2007
DOI: 10.1080/02640410600624269
|View full text |Cite
|
Sign up to set email alerts
|

Situated analysis of elite trampolinists' problems in competition using retrospective interviews

Abstract: The aims of this study were to identify and analyse elite athletes' problems in competition. A situated cognition approach placed the emphasis on athletes' actions (i.e. cognitions and behaviours), which were considered to emerge from couplings with selected elements of the context. Fifty-two exercises performed by 10 elite trampolinists were analysed. Field observations, structured interviews, and self-confrontation interviews were conducted and transcribed, and used together with behavioural descriptions der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 25 publications
1
34
0
4
Order By: Relevance
“…NDM could extend knowledge about the information perceived in the course of action that is reported by athletes. Previous studies showed that experts reported information that was significant for them (e.g., Hauw & Durand, 2007) and salient (e.g., Savelsbergh et al, 2002).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…NDM could extend knowledge about the information perceived in the course of action that is reported by athletes. Previous studies showed that experts reported information that was significant for them (e.g., Hauw & Durand, 2007) and salient (e.g., Savelsbergh et al, 2002).…”
mentioning
confidence: 97%
“…Activity is considered as a meaning construction process: meaning is built as activity unfolds, it does not precede it. These studies focused on: (a) the interpretation of athlete particular situation during the course of action (e.g., Arripe-Longueville, (d'), Saury, Fournier, & Durand, 2001), (b) the knowledge produced during the course of action (e.g., Sève, Saury, Ria, & Durand, 2003), (c) the time duration in a competition during which athletes can observe, and adapt their actions to those of their opponents (e.g., Sève & Poizat, 2005), and (d) the problems encountered by athletes during their performances (Hauw & Durand, 2007). These studies focused on dynamic and natural situations.…”
mentioning
confidence: 99%
“…L'amélioration des performances dépend de l'utilisation par les athlètes des « possibles pour l'action » dans cette alternance. Ce modèle sommairement présenté ici, a guidé la conception de dispositifs d'aides à l'entraînement (Hauw, Berthelot, & Durand, 2003 ;Hauw & Durand, 2007). L'étape d'analyse de l'activité n'est pas toujours un préalable indispensable à la modélisation dans la mesure où certaines pratiques ont déjà fait l'objet de recherches que le formateur peut exploiter : c'est le cas par exemple pour le travail des enseignants, qui est sans doute celui ayant été le plus étudié, et pour lequel les projets de formation peuvent démarrer sur la base d'une veille documentaire et une recension des recherches déjà publiées.…”
Section: Modélisation De L'activité Cible Et Formationunclassified
“…Hence, these studies made additional contributions to the research that has used this approach to show how perceived experiences during a sporting activity could be thought of as a succession of discrete sequences that have an impact on the outcome of that activity [20,21,22,23,24,25,26]. However, according to the 4 E approach, the studies underestimated the embedded components of these experiences, and particularly how they were linked to the specific environmental conditions in which the experiences occurred.…”
Section: Introductionmentioning
confidence: 99%